KONSTRUKSI KARAKTER JABO DALAM ANIMASI BINEKON - Rinkapati Swatriani (Universitas Mercu Buana, 2020)
Animation in Indonesia has developed, this time there are many agencies starting designing animations,both 2 dimension ar 3 dimension, just call one of them is Belantara Studio which has made several animated series including Binekon which tells about 5 characters representing the culture of the archipelago. Each character has its own characteristic which is a representation of the archipelago's cultural community, the focus of this research will be on the character of Jabo in the Coconut episode, is described that he can help his friends in solving problems. Primary data in this study is the perception of researchers, in this case, the researcher will give thought in studying visual signs is contained in the Binekon animation with semiotic Barthes analysis.